The Wednesday wars - Schmidt, Gary D. (New York : Clarion Books, 2007)
During the 1967 school year, on Wednesday afternoons when all his classmates go to either Catechism or Hebrew school, seventh-grader Holling Hoodhood stays in Mrs. Baker's classroom where they read the plays of William Shakespeare and Holling learns much of value about the world he lives in.
5.6
5-8
Newbery Medal/Honor, 2008
Keywords: Coming of age -- Juvenile fiction; Shakespeare, William, -- 1564-1616. -- Juvenile fiction; Junior high schools -- Juvenile fiction; Family -- New York (State) -- Long Island -- Juvenile fiction; Long Island (N.Y.) -- History -- 20th century -- Juvenile fiction; Coming of age -- Fiction; Shakespeare, William, -- 1564-1616. -- Fiction; Junior high schools -- Fiction; Schools -- Fiction; Family life -- New York (State) -- Long Island -- Fiction; Long Island (N.Y.) -- History -- 20th century -- Fiction; Shakespeare, William, -- 1564-1616. -- Fiction; Junior high schools -- Fiction; School stories; Family life -- Long Island (N.Y.) -- Fiction; Long Island (N.Y.) -- History -- 20th century -- Fiction; Bildungsromans; Bildungsromans